2016
DOI: 10.1530/eje-15-1000
|View full text |Cite
|
Sign up to set email alerts
|

X-chromosome gene dosage as a determinant of impaired pre and postnatal growth and adult height in Turner syndrome

Abstract: Objective: Short stature is a key aspect of the phenotype of patients with Turner syndrome (TS). SHOX haploinsufficiency is responsible for about two-thirds of the height deficit. The aim was to investigate the effect of X-chromosome gene dosage on anthropometric parameters at birth, spontaneous height, and adult height (AH) after growth hormone (GH) treatment. Design: We conducted a national observational multicenter study. Methods: Birth parameter SDS for gestational age, height, and AH before and after GH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…In cytogenetic studies, the chromosome karyotype 45,X among patients with TS in Japan has a lower frequency than that reported in the United Kingdom and Belgium, while karyotypes 46,X,Xi, 45,X/46,X,Xi and other mosaic 45,X have a higher frequency [19,20]. Annual evaluation of the frequency of karyotype 45,X based on which more than 400 cases were analyzed in Western countries (including the above-cited reports) showed continuous decreases by the year, recording 50% until 1982 [21], 46% until 1989 [20], and 36% between 2006 and 2013 [19,22]. This resembles the trend of change in Japan where chromosome analysis has been carried out relatively extensively as a means for screening female individuals with short statures [23].…”
Section: Discussionmentioning
confidence: 99%
“…In cytogenetic studies, the chromosome karyotype 45,X among patients with TS in Japan has a lower frequency than that reported in the United Kingdom and Belgium, while karyotypes 46,X,Xi, 45,X/46,X,Xi and other mosaic 45,X have a higher frequency [19,20]. Annual evaluation of the frequency of karyotype 45,X based on which more than 400 cases were analyzed in Western countries (including the above-cited reports) showed continuous decreases by the year, recording 50% until 1982 [21], 46% until 1989 [20], and 36% between 2006 and 2013 [19,22]. This resembles the trend of change in Japan where chromosome analysis has been carried out relatively extensively as a means for screening female individuals with short statures [23].…”
Section: Discussionmentioning
confidence: 99%
“…This association is explained by an epigenetic adaptive mechanism called fetal reprogramming. Similarly, the IUGR seen in TS fetuses is also related to dyslipidemia and T2DM in adult TS patients, presenting with a higher incidence than that of the general population [ 98 , 99 ]. Therefore, this epigenetic adaptation could partially compensate for the haploinsufficiency of the second sex chromosome in 45,X subjects, who may exhibit a constellation of clinical findings (in number and severity) depending on the specific epigenomes of each 45,X individual.…”
Section: Phenotypical Consequences Of the Epigenetic Modifications Inmentioning
confidence: 99%
“…Mutations or haploinsufficiency of SHOX gene are responsible for approximately two-thirds of the height deficits and skeletal anomalies in TS patients (17,18). In the two cases examined of the current study that presented with short stature, case 1 showed a triploid of the SHOX gene, whereas case 2 harbored the normal number of two alleles.…”
Section: Discussionmentioning
confidence: 63%